Study protocol for a randomized controlled trial investigating the effect of online interpretation bias intervention on stress reactivity in the children of parents with depression: the CoCo study - Frommelt, Tonya; Bäumler, Leonie; Rohleder, Nicolas; Schulte-Körne, Gerd; Platt, Belinda (BMC Psychiatry, 2023)
Background: Current preventive interventions for the children of parents with depression demonstrate modest effects on depression incidence. This may be because existing interventions tend to comprise general psychotherapeutic tools, rather than targeting the specific mechanisms underlying familial transmission. Improved theoretical models of familial transmission could enhance the development of targeted interventions. Although existing models assume that cognitive and biological vulnerability factors influence one another, the precise mechanisms are unknown. This project is the first to experimentally test whether negative interpretation bias has an impact on cortisol response in children of parents with depression. This study protocol reports a randomised controlled trial of an interpretation bias intervention which aims to shift participants’ interpretation bias in a more positive direction and thereby alter their stress response. Methods: Children aged 10–14 years who have i) one parent with a current or previous depression diagnosis, with at least one episode occurring during the child’s lifetime and ii) do not have a current or previous psychiatric diagnosis themselves, will be assigned to one of two conditions: an interpretation bias intervention (n = 50) or a structurally similar placebo intervention (n = 50). The interpretation bias intervention consists of a short lab-based cognitive reappraisal of interpretations training, a four-week app-based Cognitive Bias Modification of Interpretations intervention and interpretation bias specific if–then plans. Interpretation bias will be assessed before and after the intervention using the Scrambled Sentences Task. The effect of the intervention on participants’ stress response will be assessed by salivary cortisol collected at five different time points: from immediately before until 45 min after administering the Trier Social Stressor Test for Children. Stress reactivity will be measured via baseline to peak cortisol and stress recovery will be measured via the 45 min cortisol marker. We hypothesise that children who participate in the interpretation bias intervention will display a positive shift in interpretation bias and this, in turn, will alter their stress response. Children who receive the placebo intervention are expected to show a smaller positive shift in interpretation bias and stress reactivity. Discussion: The findings of the present study will contribute to models of familial depression transmission as well as informing preventive interventions. If training a more positive interpretation bias subsequently alters participants’ stress response, then incorporating such tools may increase the efficacy of existing preventive interventions. Trial registration: Deutsches Register Klinischer Studien DRKS00028842. Registered August 19, 2022.
CRIS-Team Scopus Importer:2023-06-09
Keywords: Adolescent; Cognitive behavioural therapy; Interpretation bias training intervention; Offspring; Paediatric; Parental depression; Preventive; Psychiatry; RCT